2023
DOI: 10.14295/bjs.v2i9.367
|View full text |Cite
|
Sign up to set email alerts
|

Greek consumers attitudes and motivations against PDO/PGI Agrifoods

Abstract: The study was set out to investigate the factors affecting consumers’ purchasing attitudes and their intention to buy PDO/PGI food products. A total of 615 consumers took part in the study from the municipality of Attica, Greece. The majority of the respondents consider PDO/PGI products of better quality and higher safety than the conventional ones, and they are also able to identify them. However, respondents are unsure whether these products are superior in terms of health benefits, less expensive and tastie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…The research methodology relies on the use of a quantitative method, through the sociological survey based on a questionnaire—a systematic method of collecting data from a population to gather insights and understand patterns related to human behavior, preferences, attitudes, and social contexts [ 51 ]. This research method is widely employed in the field, as demonstrated by authors from the literature [ 51 , 52 , 53 , 54 ]. In the current study, the sociological survey was meticulously designed to ensure comprehensive coverage of participants’ perceptions, experiences, and behaviors related to EU quality scheme agricultural and food products.…”
Section: Methodsmentioning
confidence: 99%
“…The research methodology relies on the use of a quantitative method, through the sociological survey based on a questionnaire—a systematic method of collecting data from a population to gather insights and understand patterns related to human behavior, preferences, attitudes, and social contexts [ 51 ]. This research method is widely employed in the field, as demonstrated by authors from the literature [ 51 , 52 , 53 , 54 ]. In the current study, the sociological survey was meticulously designed to ensure comprehensive coverage of participants’ perceptions, experiences, and behaviors related to EU quality scheme agricultural and food products.…”
Section: Methodsmentioning
confidence: 99%
“…Most existing research relies on conventional methods such as interviews or focus groups (Arfini et al, 2019;Mancini et al, 2019;Chalupová et al, 2020;Toma et al, 2023;Valverde et al, 2023), which, while significant, could not fully depict the evolving and real-time nature of consumer interests and behaviours in the digital era. Furthermore, many studies primarily concentrate on a limited selection of products or geographical regions Särkkä and Autio, 2022;Török et., 2022;Likudis and Dafni, 2023), leading to a substantial portion of certified products throughout the EU being under-investigated. As a result, a holistic understanding of consumer awareness surrounding these certified agrifood products on a pan-European scale is still somewhat unexplored terrain.…”
Section: Geographic Variationsmentioning
confidence: 99%